2014
DOI: 10.1148/radiol.14140611
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Plaque Volume and Obesity in Patients with Diabetes: The Factor-64 Study

Abstract: Purpose:To determine the relationship between coronary plaque detected with coronary computed tomographic (CT) angiography and clinical parameters and cardiovascular risk factors in asymptomatic patients with diabetes. Materials and Methods:All patients signed institutional review board-approved informed consent forms before enrollment. Two hundred twenty-four asymptomatic diabetic patients (121 men; mean patient age, 61.8 years; mean duration of diabetes, 10.4 years) underwent coronary CT angiography. Total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
(28 reference statements)
1
28
0
Order By: Relevance
“…Plaque nomenclature followed that of Miller et al (18). Proximal coronary segments were defined as C1, L1, L2, and R1 after Kwan et al (19). Analysis times ranged from 15 to 30 minutes per subject.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque nomenclature followed that of Miller et al (18). Proximal coronary segments were defined as C1, L1, L2, and R1 after Kwan et al (19). Analysis times ranged from 15 to 30 minutes per subject.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible patients who consented to receive CCTA were scanned on a 320 detector row unit (Aquilion ONE ViSION Edition; Toshiba Medical Systems, Otawara, Japan) using standard techniques [18,19] during their baseline visits on the same day that fasting blood samples were drawn (Fig. 1C and D).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover quantitative analysis of overall coronary plaque volume is now available. Studies showing increased non-calcified plaque volumes in ACS patients 53 or in obese diabetics 54 as well as response to statin therapy 34 suggest that overall coronary plaque burden may have clinical relevance.…”
Section: Imaging Of Atherosclerotic Plaque Burden and Progressionmentioning
confidence: 99%
“…Using this approach, Kwan et al showed that the percentage of calcified plaque was greater in diabetic patients with high calcium scores and larger CCTA total plaque volumes 54 (Figure 6). An ex-vivo comparison to histology showed the ability of CCTA to differentiate non-calcified, mixed and calcified plaques 85 .…”
Section: Coronary Ct Angiography Assessment Of Plaque Burden and Progmentioning
confidence: 99%
See 1 more Smart Citation